(untitled) (Proceedings of International Educators Conference, 2023)
This essay explores the impact of technology on education, highlighting its advantages, challenges, and considerations. It discusses how technology has improved access to information, facilitated interactive and personalized learning, and fostered collaboration among students and educators. The essay also addresses challenges such as the digital divide, privacy and security concerns, teacher training, and balancing technology use. By responsibly integrating technology in education, educators can create engaging and inclusive learning environments in the digital era.